Anther wall development, microsporogenesis, and microgametogenesis in abolboda and orectanthe: contributions to the embryology of xyridaceae (poales) - Oriani, Aline [UNESP]; Scatena, Vera L. [UNESP] (Univ Chicago Press, 2015)
Premise of research. Xyridaceae includes two subfamilies with a total of five genera. Xyridoideae has only the single genus Xyris, and Abolbodoideae includes the remaining genera. The inter- and intrafamilial relationships among Xyridaceae have not yet been clarified, and this study therefore aimed to investigate the anther wall and pollen grain development in Abolboda and Orectanthe species, searching for characters that can be used in taxonomic and phylogenetic analyses.Methodology. Anthers from flowers at different stages of development were examined using both LM and SEM.Pivotal results. All studied species present the following: monocotyledonous type of anther wall development, single-layered endotheciuna with band-like thickenings in the mature anther, single ephemeral middle layer, multilayered and plasmodial tapetum, successive microsporogenesis, and spherical inaperturate pollen grains. Characteristics such as reduced type of anther wall development, single-layered and secretory tapetum with uninucleate or binucleate cells, and elliptical sulcate pollen grains with a reticulate exine are present in Xyris and differentiate this genus from A bolboda and Orectanthe. The characteristics reported for Xyris are also present in Mayacaceae, which used to form the xyrid clade of Poales with Eriocaulaceae and Xyridaceae. A bolboda and Orectanthe share with Eriocaulaceae the monocotyledonous type of anther wall development with an ephemeral middle layer, an endothecium with band-like thickenings, and pollen grain exine with projections. The presence of a multilayered tapetum is exclusive to Abolboda and Orectanthe among the Xyridaceae and also among the Poales.Conclusions, The embryological characteristics support the division of Xyridaceae into two subfamilies. In contrast with the megasporogenesis and megagametogenesis, the microsporogenesis and microgametogenesis characteristics were quite variable within the xyrid (lade, with successive microsporogen.esis being the only characteristic shared by Xyridaceae, Eriocaulaceae, and Mayacaceae.
Keywords: Abolbodoideae; inaperturate pollen; multilayered tapetum; plasmodial tapetum; xyrids